COMMUNICATION AND RELATIONSHIP OF URBAN MARGINAL COMMUNITIES WITH THE GOVERNMENT - Kholifatul Fauziah; Cahyo Setiadi Ramadhan (Nusantara Hasana Journal, 2023)
This paper offers an elaboration to develop a communication strategy in empowering marginalized urban communities for creating a harmonious society in relation to the government. Besides, this paper outlines the influence factors related. Hence, marginal urban community in Ledok Timoho and Ledok Tukangan, Yogyakarta, Indonesia, are appropriate representations for empowerment communication applications that have different relations with the government. In this case, the Ledok Tukangan community is a portrayal of an urban marginal community who has a harmonious relationship with the government. Contrarily, Ledok Timoho community is an urban marginal community’s depiction who has more independent from government intervention. The research design is a case study using the strategic planning of communication theory as an analytical framework. The results revealed that the relationship with the government influenced the process and governance of community empowerment. The agents involved and the culture of the community are significant factors. This study also found a new government-community relationship model in community empowerment domain as theoretical implications arose. Furthermore, the practical implications emerged for government and non-government agents involved in the process of community empowerment communication.